ANALYSIS OF NPSH INFLUENCE ON PROGRESSIVE CAVITY PUMP PERFORMANCE FOR SUSTAINABLE SLUDGE TRANSFER IN PALM OIL MILL LAND APPLICATION SYSTEMS - Fadlah Kaumenni Sinurat; Hendra Susilo; Suardi (RADJA PUBLIKA, 2025)
In palm oil mill land application systems, the efficiency of slurry transfer from aerobic ponds to plantation channels is highly influenced by pump suction performance. This study aims to analyze the suction capability of the Progressive Cavity Pump based on the relationship between the available Net Positive Suction Head (NPSHa) and the required NPSH (NPSHr). Field measurements and calculations were conducted at pond depths ranging from −1 m to −5 m to evaluate pump performance under negative suction conditions. The results indicate that the NPSHa values consistently exceed the NPSHr value of 2.56 m across all tested depths. Specifically, at −1 m depth, NPSHa reached 8.12 m with a margin of 5.56 m, while at −5 m depth, NPSHa remained at 4.12 m with a margin of 1.56 m. The increasing NPSHa–NPSHr margin with shallower suction depths demonstrates that the PCP effectively avoids cavitation and maintains stable operation even under high negative suction pressure. The findings indicate that the PCP provides reliable and energy-efficient performance for transferring aerobic sludge in palm oil mill LA systems. Consequently, the PCP demonstrates significant potential as a superior and sustainable alternative to centrifugal pumps in organic sludge management and liquid fertilizer distribution.